Sex Differences in Work Stress - Jick, Todd D.; Mitz, Linda F. (Academy of Management Review, 1985)
This paper reviews the empirical evidence of sex differences in stress dynamics and proposes a framework for examining the sources of these differences. Nineteen studies indicate that women tend to report higher rates of psychological distress and that men are more prone to severe physical illness. Explanations for these findings are posited and reviewed. They indicate gaps, ambiguities, and inconsistencies in the existing research. An agenda for future research is suggested.